Inhibition of Nitric Oxide Synthesis Prevents the Effects of Intermittent Social Defeat on Cocaine-Induced Conditioned Place Preference in Male Mice - María Ángeles Martínez-Caballero; María Pilar García-Pardo; Claudia Calpe-López; María Carmen Arenas; Carmen Manzanedo; María Asuncion Aguilar (MDPI AG, 2024)
We have previously observed that mice exposed to social defeat stress are more sensitive to cocaine in the conditioned place preference (CPP) paradigm. In this context, it has been suggested that the nitric oxide (NO) pathway plays a role in the effects of stress. The present study evaluates the role of a neuronal NO synthase (nNOS) inhibitor (7-nitroindazole, 7-NI) in the short- and long-term behavioural effects of intermittent social defeat (ISD). Four groups of mice were employed for the study: a control group and three stressed groups, one treated with vehicle and two treated with 7-NI (7.25 or 12.5 mg/kg). After the last episode of defeat, mice were tested in the elevated plus maze (EPM), social interaction, object recognition and tail suspension tests. Three weeks later, mice were conditioned with cocaine (1 mg/kg). Stressed mice, irrespective of the treatment received, showed anxiety in the EPM, presented a deficit of social interaction and spent less time immobile in the tail suspension test. However, only stressed mice treated with vehicle developed CPP. Thus, although 7-NI did not modify the short-term behavioural effects of ISD, it prevented ISD-induced potentiation of the rewarding properties of cocaine in adulthood. These results support a specific role of nNOS in the effects of social stress on drug reward.